1990
DOI: 10.1039/c39900001518
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of the tryptophan-derived mould metabolites roquefortine and aszonalenin

Abstract: ~-[2,4,5,6,7-2H~lTryptophan has been incorporated into roquefortine and aszonalenin, by Penicillium roqueforti and by Aspergillus zonatus respectively, with retention of five deuterium atoms; the 5a-hydrogen of each of these metabolites is derived from the 2-hydrogen of tryptophan, contrary to an earlier report.A considerable degree of interest has been shown during the last two decades in the biosynthesis of tryptophan-derived metabolites that contain a 1 ,l-dimethylallyl substituent.1.2 In this connection Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…190 12. Our results therefore support the current hypothesis for the mechanism of this reverse prenylation, as discussed by Williams et al14 Feeding experiments on echinulin,40 roquefortine,41, 42 paraherquamide A,15, 43 brevianamide A,15 and austamide15 also indicated that the reverse prenylation is more likely to take place by a simple S N 2′ alkylation.…”
Section: Discussionsupporting
confidence: 90%
“…190 12. Our results therefore support the current hypothesis for the mechanism of this reverse prenylation, as discussed by Williams et al14 Feeding experiments on echinulin,40 roquefortine,41, 42 paraherquamide A,15, 43 brevianamide A,15 and austamide15 also indicated that the reverse prenylation is more likely to take place by a simple S N 2′ alkylation.…”
Section: Discussionsupporting
confidence: 90%
“…According to this hypothesis, H-2 of L-tryptophan would be retained in roquefortine or aszonalenin. This hypothesis was supported by the observation that feeding of L-[2,4,5,6,7-2 H 5 ]tryptophan in P. roqueforti and A. zonatus resulted in formation of roquefortine and aszonalenin with significant incorporation of deuterium at all of the five positions (20,21). This indicated that the H-2 was retained during the prenylation reaction.…”
Section: Discussionsupporting
confidence: 70%
“…Feeding experiments have shown that L-tryptophan was incorporated into aszonalenin (20,21), indicating that the original (S) configuration of the ␣-atom in L-tryptophan was converted to (R) configuration at position C11 of aszonalenin. Prenylation and acetylation steps led to formation of aszonalenin and acetylaszonalenin with the same configuration at C11 as in (R)-benzodiazepinedione or D-tryptophan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkaloid roquefortine D (5) was subsequently isolated-it was suggested that its biogenesis passes through mevalonic acid, tryptophan and histidine (Ohmomo et al 1978). More recently, some evidence supporting this hypothesis has been provided (Bhat et al 1993). Moreover, Bellinck (1975) studied the chemistry of the pigments of P. roqueforti and showed that these compounds are polyphenolic in nature (Fig.…”
Section: Secondary Metabolites and High Value-added Productsmentioning
confidence: 99%